2019
DOI: 10.1001/jamaneurol.2019.0658
|View full text |Cite
|
Sign up to set email alerts
|

Association of Closed-Loop Brain Stimulation Neurophysiological Features With Seizure Control Among Patients With Focal Epilepsy

Abstract: IMPORTANCE A bidirectional brain-computer interface that performs neurostimulation has been shown to improve seizure control in patients with refractory epilepsy, but the therapeutic mechanism is unknown. OBJECTIVE To investigate whether electrographic effects of responsive neurostimulation (RNS), identified in electrocorticographic (ECOG) recordings from the device, are associated with patient outcomes. DESIGN, SETTING, AND PARTICIPANTS Retrospective review of ECOG recordings and accompanying clinical meta-da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 36 publications
2
128
0
Order By: Relevance
“…41 In addition, recent studies have shown that features in the ECoG data may provide objective biomarkers that can be used to assess the clinical response to stimulation. 42,43 In addition, it may be possible to use an individual patient's ECoG data to identify periods of heightened seizure risk. 44,45 In the future, these data may be used to supplement the patient's clinical report.…”
Section: Discussionmentioning
confidence: 99%
“…41 In addition, recent studies have shown that features in the ECoG data may provide objective biomarkers that can be used to assess the clinical response to stimulation. 42,43 In addition, it may be possible to use an individual patient's ECoG data to identify periods of heightened seizure risk. 44,45 In the future, these data may be used to supplement the patient's clinical report.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulating into well‐developed electrographic seizures may not always disrupt electrographic seizure activity, perhaps because the seizure has already propagated beyond the region that can be impacted by spatially limited stimulation. It is possible that delivering acute disruptive stimulation into abnormal (interictal) electrographic activity (not only seizures) is effective because of providing longer‐term neuromodulation 19,28 . This hypothesis is supported by the observation that the total duration of stimulation received was a median of 4.5 min/d (IQR = 1.4‐9.3 min/d) in the real‐world patients, which is significantly greater than in the Pivotal trial population (median = 3.0 minutes of stimulation per day, IQR = 1.5‐5.1 min/d) at 2 years postoperatively ( P = .024), although substantially less than with open‐loop scheduled stimulation approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the effects of brain stimulation on epileptogenic networks remain largely unknown, and the relative contributions of lead configuration and stimulation pathway (ie, anode/cathode electrode designations) to therapeutic efficacy are currently undefined . Modeling studies suggest that the volume of tissue activated by DBS electrodes is on the order of cubic millimeters .…”
Section: Discussionmentioning
confidence: 99%